Nos passos do garimpo: a manutenção da precariedade na extração de caulim em Junco do Seridó-PB - Souza, Edivane Saraiva de (2011)
This research aims at analyzing the work reality of kaolin prospectors in the town of Junco do Seridó. The world of prospecting is well known for its informality and precariousness. Workers undergo excessively long working hours and constant unsafety conditions, being an easy target of labor accidents, most of the times the fatal ones. Not only does this problem affect the prospector but also his family as well, which becomes forsaken and are not entitled to any social benefit. This project was developed from June 2010 to September 2011. Its first step was a vast bibliographical research collect related to the topic. Its second step corresponded to entering the field of work in order to, from that point on, know deeply the work reality in the mines of the town. To achieve this, semi-structured interviews and informal talks with prospectors, local businessmen, residents and politicians from the town of Junco were held. The mentioned instruments aimed at understanding how the prospectors see themselves in their job and how they analyze their work universe.